2017
DOI: 10.2147/ccide.s129598
|View full text |Cite
|
Sign up to set email alerts
|

Presurgical cleft lip and palate orthopedics: an overview

Abstract: Patients with cleft lip and/or palate go through a lifelong journey of multidisciplinary care, starting from before birth and extending until adulthood. Presurgical orthopedic (PSO) treatment is one of the earliest stages of this care plan. In this paper we provide a review of the PSO treatment. This review should help general and specialist dentists to better understand the cleft patient care path and to be able to answer patient queries more efficiently. The objectives of this paper were to review the basic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 23 publications
0
42
0
5
Order By: Relevance
“…In the opposite, case 2 showed a higher difficulty for a 3-year old child wearing and adapting to the appliance, resulted in poor prognosis. Unilateral CLP can be treated using passive appliance and active appliance with lip strapping 5 .In case 1, PSO appliance with lip strap was chosen because of significant cleft in palatum extending to lip with protruding premaxilla. While, case 2 introduced PSO appliance without additional features because defect only occurred in palatum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the opposite, case 2 showed a higher difficulty for a 3-year old child wearing and adapting to the appliance, resulted in poor prognosis. Unilateral CLP can be treated using passive appliance and active appliance with lip strapping 5 .In case 1, PSO appliance with lip strap was chosen because of significant cleft in palatum extending to lip with protruding premaxilla. While, case 2 introduced PSO appliance without additional features because defect only occurred in palatum.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it can function as a rigid platform, towards which the child can press the nipple and feed; and also directs the tongue in to the correct position. Proper tongue position will be useful for developing normal speech and restoring well-functioned mastication 5,6 . The case revealed that The PSO appliance could approximate the segments of the cleft maxilla by allowing spontaneous growth of palatal shelves prior to the reconstructive and definitive surgery.…”
mentioning
confidence: 99%
“…Primeiro por impor a necessidade de longo tratamento multidisciplinar, que de forma alguma finaliza com o fechamento da fissura de lábio, por menor que ela seja. Nos protocolos de tratamento da fissura orofacial, frequentemente, estão incluídas as cirurgias corretivas de lábio, que pode incluir a cirurgias primárias e secundárias; a cirurgia corretiva do palato, que da mesma forma, pode incluir corretivas de fístulas remanescentes; as longas intervenções fonoaudiológicas; os tratamentos odontológicos, ortodônticos e ortognática, entre outros (FREITAS et al, 2012ALZAIN et al, 2017SISCHO;WILSON-GENDERSON;BRODER, 2017 1992). Associado a aparência facial marcante, os indivíduos com síndrome Opitz GBBB, de acordo com dados da literatura, podem apresentar atraso no desenvolvimento e deficiência intelectual, além de alterações no sistema nervoso central (OPITZ, 1987;GUION-ALMEIDA;RICHIERI-COSTA, 1992;MERONI, 2004;HSIEH et al, 2008).…”
Section: Memória De Longo Prazo Episódica Visuoespacialunclassified
“…Placa ortopédica. La placa de modelaje naso alveolar, es una técnica que consiste en la colocación de una placa (usualmente de acrílico) que cubre la parte fisurada de la boca del niño y cuyo objetivo es reposicionar los segmentos naso-labiales y maxilares, y acercarlos (125). La placa ortopédica fue preconizada por Mc Neil en 1959, luego, en 1975 Georgide y Latham introdujeron un aparato activo retenido por pines para, simultáneamente retraer la premaxila y expandir los segmentos posteriores en un periodo de varios días.…”
Section: Tratamiento Prequirúrgico Del Niño Con Fisura Labio Alveounclassified
“…Por otro lado, diferentes trabajos de 2018, demostraron que después de la queiloplastía, la placa ortopédica naso-alveolar mejora la simetría nasal y el ángulo de la columela, reduce la brecha (gap) de la fisura alveolar, y mejora la forma del arco dental (129,132). Otros coinciden en que la placa reduce el espacio entre los lados de la fisura, pero no pueden asegurar si estos resultados representan un beneficio real a largo plazo (125).…”
Section: Tratamiento Prequirúrgico Del Niño Con Fisura Labio Alveounclassified